EFFECT OF THE GOVERNMENT INTERVENTION PROGRAM TO THE CROP INSURANCE PARTICIPATION LEVEL - Rachman, Muhammad Ibrahim; Nuryartono, Nunung; Arifin, Bustanul; Bakhtiar, Toni (School of Business, Bogor Agricultural University (SB-IPB), 2021)
In addition to premium subsidies, Indonesia's government implements other intervention programs as a stimulus to boost farmers’ participation in Rice Farmers Business Insurance (AUTP). Therefore, this study aimed to investigate the effect of the government intervention program in 2019 that requires participation in AUTP as a prerequisite for redeeming subsidized fertilizer. This study also aimed to ascertain the socioeconomic factors that influence farmers to participate. Meanwhile, primary data were obtained through questionnaires distributed from March 23 to April 6, 2020, and completed by 103 farmers in 14 villages in Sliyeg, Indramayu. The data were analyzed with McNemar Test to determine the effect of farmers’ participation in AUTP when the government intervention program was implemented and terminated. Furthermore, Logistic Regression Analysis is used to ascertain the socioeconomic factors that influence farmers to participate. The result showed that the program affects their participation in AUTP. This level is higher when the program is enforced and decreased when terminated. The socio-economics variables that influenced farmers to participate in AUTP when implemented in the government program are land ownership status and land size, while only land size influenced them when terminated. Keywords: agriculture risk, consumer behavior, government stimulus, participation rate, premium subsidy